Primeiro censo brasileiro em cirurgia refrativa - Victor, Gustavo (2005)
PURPOSE: To perform the first Brazilian refractive surgery survey. METHODS: Between August 2001 and February 2002, a questionnaire was mailed to 7890 Brazilian ophthalmologists. The questionnaire presented questions about demographic aspects, technology, instruments, market, trends, practice patterns and cost of refractive surgery. RESULTS: Nine hundred and twenty questionnaires (11.67%) were answered. LASIK is the preferred technique for correction between +5.00 and -7.00 D. The mostly used excimer laser is Nidek® EC 5000, and Hansatome is the mostly used microkeratome. Others aspects like: demographic, techniques, practice patterns, trends, market, and pre-, intra- and postoperative care, were analyzed. CONCLUSION: With this survey, the Brazilian ophthalmologists can observe and monitor these aspects of refractive surgery in Brazil, and compare them with others surveys.